1993
DOI: 10.1073/pnas.90.24.12045
|View full text |Cite
|
Sign up to set email alerts
|

apl-1, a Caenorhabditis elegans gene encoding a protein related to the human beta-amyloid protein precursor.

Abstract: The major component of senile plaques found in the brains of Alzheimer disease patients is the 3-amyloid peptide, which is derived from a larger amyloid precursor protein (APP). Recently, a number of APP and APP-related proteins have been identified in different organisms and constitute the family of APP proteins. We have isolated several cDNAs encoding an APP-related protein in the nematode Caenorhabdiis elegans and have designated the corresponding gene as apl-i. The apl-i transcripts undergo two forms of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
140
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 47 publications
0
140
0
Order By: Relevance
“…C. elegans also expresses an APP homolog: the amyloid precursor-like protein 1 (APL-1). 147 Both of these homologs are similar to APP throughout their length, but the A␤ regions lacks similarity to human APP. In Drosophila, overexpression of APPL or several human APP constructs (with and without mutations) causes an axonal transport phenotype similar to that seen in kinesin and dynein mutants, 148 implicating APP in axonal transport.…”
Section: Nonrodent Transgenic Modelsmentioning
confidence: 99%
“…C. elegans also expresses an APP homolog: the amyloid precursor-like protein 1 (APL-1). 147 Both of these homologs are similar to APP throughout their length, but the A␤ regions lacks similarity to human APP. In Drosophila, overexpression of APPL or several human APP constructs (with and without mutations) causes an axonal transport phenotype similar to that seen in kinesin and dynein mutants, 148 implicating APP in axonal transport.…”
Section: Nonrodent Transgenic Modelsmentioning
confidence: 99%
“…APP belongs to a family of conserved type I transmembrane proteins including Apl-1 in Caenorhabditis elegans (Daigle and Li, 1993), Appl in Drosophila (Rosen et al, 1989), and APP (Tanzi et al, 1987), APP-like protein 1 (APLP1) (Wasco et al, 1992), and APLP2 (Wasco et al, 1993;Slunt et al, 1994) in mammals. Within the nervous system, APP can be detected on the membranes of synaptic preparations (Kirazov et al, 2001) and has been shown to localize to the postsynaptic densities, axons, and dendrites (Schubert et al, 1991;Shigematsu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The C. elegans homolog of APP, APL-1 lacks Aβ peptide sequences and β-secretase recognition sites which renders them incapable of producing amyloid peptides and hence plaques (Daigle and Li, 1993;McColl et al, 2012). Also, Aβ peptides have never been detected in C. elegans (McColl et al, 2012).…”
Section: Elegans As a Model For Alzheimer's Diseasementioning
confidence: 99%